A distribution dynamics approach to regional GDP convergence in unified Germany - Falko Juessen (Institute for the Study of Labor (IZA), 2009)
This paper uses nonparametric techniques to study GDP convergence across German labor market regions and counties during the period 1992-2004. The main result is that regional convergence in unified Germany has been substantial. In the first years after German unification the distribution of GDP has been characterized by a pronounced bimodality. The dispersion of the GDP distribution has become substantially smaller over time. Although some bimodality remains in most recent years, this bimodality is weak in comparison to previous years. Nevertheless, disparities among regions located in the Eastern and Western part of the country are still apparent.
urn:nbn:de:101:1-2009060884
Keywords: O47; R11; C14; 330; Regional convergence; distribution dynamics; nonparametric econometrics; stochastic kernel; Regionale Entwicklung; Entwicklungskonvergenz; Regionale Disparität; Schätzung; Neue Bundesländer; Alte Bundesländer; Deutschland